2016
DOI: 10.1002/2015jd024575
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Sahelian‐Sudan moisture: Insights from a moisture‐tracing atmospheric model

Abstract: The summer rainfall across Sahelian‐Sudan is one of the main sources of water for agriculture, human, and animal needs. However, the rainfall is characterized by large interannual variability, which has attracted extensive scientific efforts to understand it. This study attempts to identify the source regions that contribute to the Sahelian‐Sudan moisture budget during July through September. We have used an atmospheric general circulation model with an embedded moisture‐tracing module (Community Atmosphere Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…While the Western Mediterranean basin influences the European continent [42] (mainly over the Iberian, Italian, and Balkan Peninsulas and France) and Northern-Western Africa [3,23] and the Central Mediterranean Sea contributes more to the Italian Peninsula and Northern-Central Africa [3,42], which exhibits a huge influence on extreme precipitation in the Alpine region [48] due to the intensification of the moisture uptake from the Mediterranean basin during the autumn and winter [22]. However, the Mediterranean influence on even more distant regions is also known and the moisture that reaches regions such as the Sahel [49,50], Central Asia, and the Arabian Peninsula [51] is not negligible. In addition, it has been demonstrated that changes in the moisture evaporation from the Mediterranean Sea affect the wetness or dryness of conditions over areas where it sinks [23,52,53].…”
Section: Moisture Transport and Effectsmentioning
confidence: 99%
“…While the Western Mediterranean basin influences the European continent [42] (mainly over the Iberian, Italian, and Balkan Peninsulas and France) and Northern-Western Africa [3,23] and the Central Mediterranean Sea contributes more to the Italian Peninsula and Northern-Central Africa [3,42], which exhibits a huge influence on extreme precipitation in the Alpine region [48] due to the intensification of the moisture uptake from the Mediterranean basin during the autumn and winter [22]. However, the Mediterranean influence on even more distant regions is also known and the moisture that reaches regions such as the Sahel [49,50], Central Asia, and the Arabian Peninsula [51] is not negligible. In addition, it has been demonstrated that changes in the moisture evaporation from the Mediterranean Sea affect the wetness or dryness of conditions over areas where it sinks [23,52,53].…”
Section: Moisture Transport and Effectsmentioning
confidence: 99%
“…The Sahelian rainfall variability has been linked to a number of climate processes on local, regional, and global scales. Salih et al [2] used the general circulation atmospheric model CAM3 and the Lagrangian transport and dispersion model FLEXPART (FLEXible PARTicle dispersion model) to estimate the moisture contributions from different source regions to the Sahelian-Sudan rainfalls and showed that distant regions, such as the Mediterranean, can be a significant moisture source, with a notable seasonality.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors performed studies to identify moisture sources over the Sahel [2,[19][20][21][22][23]. However, the relative contributions of these sources vary from one study to another.…”
mentioning
confidence: 99%
“…has been tested and used for climate simulations and paleoclimate studies (Pausata et al, 2011;Sturm, Zhang, & Noone, 2010), as well as the moisture tracing in other regions (Salih et al, 2016). The relatively long period covered in this study, from 1961 to 2012, allows for a robust analysis of historical trend as well as the interannual variability of local moisture recycling, and its relationship with moisture transport and other impact factors, such as sea surface temperature and the natural variability of the climate system.…”
Section: Introductionmentioning
confidence: 99%